Evaluation of hooves’ morphometric parameters in different hoof trimming times in dairy cows - Ahmadreza Mohamadnia; Amin Khaghani (Veterinary Research Forum, 2014)
Wide variety of timings and techniques has been used based on the housing, production, availability of requirements etc. This current study was done for a morphologic evaluation of the cow's digit in different trimming times. A dairy herd with 2200 milking cow, free stalls barns, average daily production of 36 liters per cow was selected. Forty cows were assigned to four groups based on hoof trimming times as, 100-120 days in milk (Group I), cows before drying (Group II), visual long toed cows (Group III) and delayed pregnant cows (Group IV). Toe length from coronary band to the toe tip (A), dorsal hoof angle (D), toe height from coronary band in toe region to the ground level (B), heel height from coronary band in heel region to the ground level (C) and heel height to toe length proportion was measured. The highest toe length was recorded in medial digit of group IV (9.19 ± 0.68 cm) and the lowest one recorded in lateral digit of group I (8.28 ± 0.62 cm). Distribution of the cows in different groups under study was based on their toe length, as the highest and lowest distribution were recorded in groups III and I, respectively. The highest measurements in all indices were recorded in group IV that followed by group III except for toe height that was higher in group II following group IV. The lowest toe length was recorded in group I that needs more attention due to the risk of over trimming and its supposed complications in this group.